Nutritional value and prediction of digestible and metabolizable energy of full-fat deactivated soybeans for pigs - Teresinha Marisa Bertol; Jorge Vitor Ludke; Arlei Coldebella; Herbert Rech (Animal Bioscience)
Objective The objective of this work was to determine the energetic values of 14 full-fat deactivated soybeans samples, the effect of partial removal of the hull, and to develop equations for predicting digestible (DE), metabolizable (ME), and ME corrected for nitrogen balance (MEn) for pigs. Methods Ten metabolism experiments were conducted over a two-year period to evaluate 14 batches of full-fat deactivated soybeans, following the method of the total collection of feces and urine. One hundred and ninety-two pigs with an average initial body weight of 51.4±5.4 kg were assigned to dietary treatments. Results Partial dehulling of soybeans did not affect DE, ME, and MEn values. The variables that best explained the variations (p<0.05) in DE were ureatic activity (UA) and crude fiber. The variables that showed the greatest association (p<0.05) with ME and MEn were UA, protein solubility, and processing pressure. The observed effect of UA on energy values was quadratic (p<0.05). Phosphorus also showed association (p<0.05) with DE and ME and the energy applied per kg of sample showed association (p<0.05) with ME and MEn. Conclusion The overall mean values of DE, ME, and MEn were 4,558, 4,457, and 4,344 kcal/kg, respectively. The partial removal of the hull prior to soy deactivation did not affect the digestibility or the energy values. This study shows that the processing conditions are the main factors affecting the energetic value of full-fat deactivated soybeans for pigs, which can be accurately predicted using a combination of chemical composition, quality indicators, and processing parameters.